Exploring the Student Experience in Vocabulary Learning Using the Wordwall Platform - Purwaning, Alynia; Muamaroh, Muamaroh; Ratih, Koesoemo; Prastiwi, Yeny; Hidayat, Nur (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2026)
In the 21st century, technology is not just a tool, but an essential part of the teaching and learning process. The goal as educators is to bridge the gap between their natural curiosity and formal learning by making the experience interactive, personalised, and fun. Using interactive media for students is important. This material specifically focuses on leveraging a gamification platform like Wordwall, a web-based application that transforms standard content into dynamic, game-based learning activities. This research has goal to find out the Wordwall implementation as an interactive media for teaching English, especially in teaching vocabulary. This research is a qualitative study employing a case study design to explore the use of instructional media in depth. The population of this research consists of English teachers and third-grade students at an elementary school in Mojokerto, with a specific sample of one English teacher who has integrated Wordwall media into the teaching process. Data collection techniques were carried out through direct classroom observations to monitor learning interactions, as well as in-depth interviews with the teacher to gather detailed information. Furthermore, the collected data were processed using qualitative data analysis techniques, which include data reduction, systematic data display, and drawing conclusions to address the research focus. The results showed that there are many advantages in using the Wordwall application for the teaching and learning process, especially for learning vocabulary. The advantages included.